SELF-ESTEEM DAN KESEPIAN PADA MAHASISWA SELAMA MASA PANDEMI - Mutiara Mirah Yunita; Kezia Isabel; Bertha Ernest Keziah; Melani Cristina Natasya; Selviana Candra Wijaya (Jurnal Psikologi Malahayati, 2022)
ABSTRACT: SELF-ESTEEM AND LONENESS IN COLLEGE STUDENTS DURING PANDEMIC This study aims to see the relationship between self-esteem and loneliness in X university students in Jakarta during the pandemic. This study uses quantitative research methods with purposive sampling technique so as to obtain participants as many as 214 students consisting of 64 male participants and 150 female participants. This study uses two measuring instruments, namely the Rosenberg Self-Esteem Scale which is used to measure the participants' self-esteem and the UCLA Loneliness Scale Version 3 which is used to measure the loneliness of the participants. The results of this study indicate that there is a significant negative relationship between self-esteem and loneliness of X university students in Jakarta during the pandemic (r (212) = -.581, p < .01), which means that the higher the participant's self-esteem, the lower the participant's self-esteem. participants' level of loneliness, and vice versa. The results of this study are also in line with the results of previous studies where there is a negative relationship between self-esteem and loneliness. The implication of the results of this study is that this research can help explain that good self-esteem helps prevent loneliness during the pandemic and helps students to carry out lectures well without being overwhelmed by loneliness because they have to undergo lectures online. Keywords: College Students, Loneliness, Pandemic, Self-Esteem Penelitian ini bertujuan untuk melihat hubungan antara self-esteem dengan kesepian pada mahasiswa universitas X di Jakarta selama masa pandemi. Penelitian ini menggunakan metode penelitian kuantitatif dengan teknik purposive sampling sehingga mendapatkan partisipan sebanyak 214 mahasiswa yang terdiri dari 64 partisipan laki-laki dan 150 partisipan perempuan. Penelitian ini menggunakan dua alat ukur yaitu Rosenberg Self-Esteem Scale yang digunakan untuk mengukur self-esteem dan UCLA Loneliness Scale Version 3 yang digunakan untuk mengukur. Hasil penelitian ini menunjukkan bahwa ter-dapat hubungan negatif yang signifikan antara self-esteem dengan kesepian mahasiswa universitas X di Jakarta selama masa pandemi (r (212) = -.581, p < .01), yang berarti semakin tinggi self-esteem partisipan maka semakin rendah tingkat kesepian partisipan, begitu pula sebaliknya. Hasil penelitian ini juga sejalan dengan hasil penelitian sebelumnya dimana terdapat hubungan yang negatif antara self-esteem dengan kesepian. Implikasi hasil penelitian ini adalah penelitian ini dapat membantu menjelaskan bahwa self-esteem yang baik membantu mencegah terjadinya kesepian di masa pandemi dan membantu mahasiswa menjalani perkuliahan dengan baik tanpa diliputi oleh rasa kesepian karena harus menjalani perkuliahan secara daring. Kata Kunci: Mahasiswa, Kesepian, Pandemi, Harga Diri